Association of loneliness with incident cardiovascular diseases in middle-aged and older Chinese adults - Bo Xie; Yehua Fang; Fang Lin; Ming Yang; Yanchao Liang; Bin Liu (PLoS ONE, 2026)
Loneliness, a significant social determinant of health, has been increasingly recognized for its potential to influence cardiovascular disease (CVD) risk. This study aimed to delineate the relationship between loneliness and the incidence of CVD, specifically heart disease and stroke, among Chinese adults aged 45 and older. Utilizing data from the China Health and Retirement Longitudinal Study (CHARLS), loneliness was assessed using a validated single-item measure. Incident CVD events, including heart disease and stroke, were ascertained through standardized interviews. We employed Cox proportional hazards models to calculate hazard ratios (HRs), adjusting for a comprehensive set of covariates. A longitudinal analysis of 8,046 participants initially free of CVD was conducted. During a 7-year follow-up period, 1,033 participants experienced incident CVD events. Loneliness was found to be an independent risk factor for CVD, with individuals reporting loneliness exhibiting a 42.9% higher risk of developing CVD (adjusted HR: 1.429; 95% CI, 1.251–1.632). Specifically, the risk of heart disease was elevated by 44.7% (adjusted HR: 1.447; 95% CI, 1.229–1.703), and the risk of stroke was increased by 27.9% (adjusted HR: 1.279; 95% CI, 1.035–1.580). This association was particularly pronounced among those without a history of hypertension, where the risk of CVD was elevated by 58.2% (adjusted HR: 1.582; 95% CI, 1.317–1.900). Our findings indicate that loneliness is significantly associated with an increased risk of CVD, specifically heart disease and stroke, among Chinese adults aged 45 and older. These results highlight the need to consider psychosocial factors in CVD prevention strategies.